2019
DOI: 10.1093/pcmedi/pbz009
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is an infectious disease and the empiric therapy paradigm should be changed

Abstract: Helicobacter pylori infection is an infectious disease. Given the alarmingly high antibiotic resistance in H. pylori, gastroenterologists should change the empiric H. pylori treatment paradigm to an antimicrobial susceptibility testing-guided precision treatment. Antimicrobial stewardship programs for H. pylori should be implemented locally, regionally, and nationally to monitor the antibiotic resistance pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Given the limited number of antibiotics that are appropriate for H. pylori eradication in children, and the worldwide increase of antibiotic resistance, the recent ESPGHAN/NASPGHAN guidelines have recommended antimicrobial susceptibility testing to guide the H. pylori eradication treatment in children ( Jones et al, 2017 ). However, due to the fastidious culture of H. pylori and the lack of an easy and cost-effective testing method, antimicrobial susceptibility testing for H. pylori is almost universally unavailable in medical centers ( Montes and Pérez-Trallero, 2017 ; Li et al, 2019 ; Tang et al, 2020a , b ). Under such circumstances, profiling regional or population-specific antibiotic resistance patterns is of great importance in guiding the development of effective empiric treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited number of antibiotics that are appropriate for H. pylori eradication in children, and the worldwide increase of antibiotic resistance, the recent ESPGHAN/NASPGHAN guidelines have recommended antimicrobial susceptibility testing to guide the H. pylori eradication treatment in children ( Jones et al, 2017 ). However, due to the fastidious culture of H. pylori and the lack of an easy and cost-effective testing method, antimicrobial susceptibility testing for H. pylori is almost universally unavailable in medical centers ( Montes and Pérez-Trallero, 2017 ; Li et al, 2019 ; Tang et al, 2020a , b ). Under such circumstances, profiling regional or population-specific antibiotic resistance patterns is of great importance in guiding the development of effective empiric treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Without the specific antibiotic treatment, this infection can cause chronic active gastritis which can subsequently leads to peptic ulcer in 15-20% of the patients and gastric malignancy and mucosa-associated lymphoid tissue (MALT) lymphomain approximately 1-3%. Chronic H.pylori infection has been identified as one of the most important etiological factors for gastric cancer which is third leading cause of cancer death globally 8 . Javed et al, have reported prevalence of H. Pylori infection 92% among patients of gastritis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The phages which are specifically isolated against H.pylori are named as* phi HPE1 and *phi HPE2 and their host ranges were investigated against four different strains of H.pylori in which all were susceptible to either *phi HPE1 or *phi HPE2 [26], another H.pylori specific phage was isolated which was named KHP30 [27], despite its very fruitful characteristics still there is no available collection of phages specifically against H.pylori and very little research work and scientific literature is available about H.pylori phages the given phages which are isolated uptill now are fully characterised and the next target is to study in detail and examine the virulence factors responsible in eradicating H.pylori [128].…”
Section: Phages Exploited Against Helicobacter Pylorimentioning
confidence: 99%
“…This may lead to antimicrobials that have the narrowest range imaginable. Zinc fingers [22][23][24][25], transcription activation-like effector nucleases [26], peptide nucleic acids [27],…”
Section: Introductionmentioning
confidence: 99%